INFLUENCE OF EXCESSIVE NIGHTTIME ACTIVITY ON THE RISK OF ISCHEMIC CEREBRAL STROKE EVENT AND ITS COURSE FEATURES - Volosovets, A.O.; Zozulya, I.S.; Volosovets, O.P.; Savchenko, D.S.; Kramareva, O.G. (World of Medicine and Biology, 2020)
Clinical neurological and neuroimaging examination of 300 patients with ischemic stroke was performed. The control group included 40 patients without signs of acute cerebral stroke (men - 21, women - 19) aged 46 to 76 years (mean age being 62.6 ± 10.2 years). The data obtained confirmed that the important role of excessive nighttime activity (ENA) is characteristic of all groups of patients, but 100% correlation is observed in patients with nocturnal strokes. In patients with ENA there are two peaks of blood pressure increase: - 9:00 and 21:00. Patterns of blood pressure disorders at night were as follows: 68.4% (n = 13) - night peaker, 26.3% (n = 5) - non dipper, 5.2% (n = 1) - dipper subtype. Against the background of an optimized stroke prevention program, the incidence of recurrent ischemic strokes was by 2.09 times lower than in the control group within 2 years. The present study results show the importance of ENA for the diagnosis and pathogenesis of acute ischemic stroke.
Keywords: stroke; excessive nighttime activity; onset time; stroke risk; prevention